PERANCANGAN GAME EDUKASI GOI BERBASISKAN FLASH - Ditansya Lubis; Riska Sri Rahmawati; Soni Mulyawan Setiana (Janaru Saja Jurnal Program Studi Sastra Jepang, 2017)
In learning japanese language, vocabulary is the most important thing in learning a language especially Japanese language. But in the process of learning vocabulary, students sometimes feel bored with the usual methods done in learning. To overcome the saturation, then made an educational game that provides education in the form of basic vocabulary of Japanese language. The design of this game successfully done by using the system development method is waterfall where progress is seen continue to flow down like a waterfall, which passes through the demands definition phase, system & software design, implementation & unit testing, integration & system testing, operation & maintance. This game is implemented by using the programming language actionscript using Adobe Flash CS6 software.